Preparation and Characterisation of Nobiletin-Loaded Nanostructured Lipid Carriers. (17th August 2017) - Huang, Wei; Dou, Huating; Wu, Houjiu; Sun, Zhigao; Wang, Hua; Huang, Linhua
Abstract : The objective of this manuscript was to investigate and optimise the potential of nanostructured lipid carriers (NLCs) as a carrier system for nobiletin (NOB), which was prepared by high-pressure homogenisation method. Additionally, this study was focused on the application of NOB-loaded NLC (NOB-NLC) in functional food. Response surface method with a three-level Box–Behnken design was validated through analysis of variance, and the robustness of the design was confirmed through the correspondence between the values measured in the experiments and the predicted ones. Properties of the prepared NOB-NLC, such as Z -average, polydispersity, entrapment efficiency, zeta potential, morphology, and crystallinity, were investigated. NOB-NLC exhibited a spherical shape with a diameter of 112.27 ± 5.33 nm, zeta potential of −35.1 ± 2.94 mV, a polydispersity index of 0.251 ± 0.058, and an EE of 81.06%    ±    6.02%. Results from X-ray diffraction and differential scanning calorimetry of NOB-NLC reviewed that the NOB crystal might be converted to an amorphous state. Fourier transform infrared spectroscopic analysis demonstrated that chemical interaction was absent between the compound and lipid mixture in NOB-NLC.